2019
DOI: 10.1039/c9bm00822e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photoacoustic imaging using indocyanine green (ICG) loaded functionalized mesoporous silica nanoparticles

Abstract: Herein, we demonstrate the role of surface modification of nanocarriers on their ability to load and protect sensitive payloads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 65 publications
2
52
0
Order By: Relevance
“…In the preceding section, we performed absorption measurements at low concentrations to ensure that ICG was present in its monomeric form. However, some imaging experiments, particularly photoacoustic imaging studies [18–20] are performed at high concentrations (∼1 mM). Thus, it is useful to understand the photophysical behavior of ICG at higher concentrations, specifically, the roles of aggregation and self‐quenching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the preceding section, we performed absorption measurements at low concentrations to ensure that ICG was present in its monomeric form. However, some imaging experiments, particularly photoacoustic imaging studies [18–20] are performed at high concentrations (∼1 mM). Thus, it is useful to understand the photophysical behavior of ICG at higher concentrations, specifically, the roles of aggregation and self‐quenching.…”
Section: Resultsmentioning
confidence: 99%
“…ICG has been FDA approved for ∼60 years and is used pre‐clinically and clinically in NIR optical imaging applications, including for angiography, [2] lymphatic, [3–6] biliary [7,8] and intestinal [9] functional imaging, dental imaging, [10] and oncological image guided surgery [11–13] . Additionally, there is increasing interest in broader applications of fluorescence guided surgery [14–17] as well as photoacoustic imaging [18–20] with ICG and ICG conjugates. In 2018, it was reported that ICG has a long wavelength emission tail which extends past the NIR region [21,22] .…”
Section: Introductionmentioning
confidence: 99%
“…It has a wide range of applications in the biomedical field and recently has been used to follow the trafficking of nanoscale materials inside cells. The encapsulation of PA imaging agents inside functionalized MSNs has been studied to obtain the most efficient PA imaging performance [ 162 , 163 ]. Thus, there is a potential to use PA methodology in the future to study drug release in vivo relying on its co-delivery with PA imaging molecules.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…As a light absorber, ICG is a near-infrared dye that is nearly harmless to the human body and easily metabolized. 26 , 27 , 45 After loading the ICG package into NPs, they are excited by PA instruments to enable PA imaging, which is the basis for the ability of this nanoparticle to act as a molecular probe for PA imaging. Through experiments, we found that in in vitro PA imaging, NPs were able to produce PA signals at low ICG concentrations, and the resulting PA signals could be linearly enhanced as ICG concentrations increased, suggesting that the NPs were able to absorb light and to convert into PA signals.…”
Section: Resultsmentioning
confidence: 99%